Business feasibility study of Dreamhome Villa - Stevanny Lithania; Sonny V Sutedjo (President University, 2022)
The growing tourism sector has created many business opportunities that can be done. Accommodation is an important part of meeting the needs of tourists. During three years, from 2018 - 2021, the number of tourist visits to accommodation in Bandung City almost doubled; where in 2018, the number of tourist visits to accommodation in Bandung City was 4,801,108 tourists, and in 2019 it became 8,411,064 tourists, and currently the staycation phenomenon is becoming a growing holiday trend. This research aims to analyze the DreamHome villa using financial feasibility analysis as the main analysis and industrial feasibility as a secondary analysis. The feasibility of using financial investments such as Present Net Value (NPV) and Payback Period (PP). For industry feasibility, using Porter's Five Forces and SWOT analysis resulted in low competitive rivalry yet a high risk of substitution. Financial analysis shows a Present Net Value of Rp 1.274.756.392 (NPV> 0), ROA 12,74 %, ROS 55,60 %, and the Payback Period is less than one year. Then for the feasibility of the industry using Porter's Five Forces and SWOT analysis, the average results of the competitive competition and moderate risk of substitution are media. From both analysis on finance and industry feasibility, the analysis results indicated that the business has a profitable prospect and is financially feasible.